2022
DOI: 10.3390/vaccines10122060
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Infections (HAIs): Challenges and Measures Taken by the Radiology Department to Control Infection Transmission

Abstract: Infections contracted during healthcare delivery in a hospital or ambulatory setting are collectively referred to as healthcare-associated infections (HAIs). Healthcare workers and patients alike are vulnerable to serious problems as a result of the risk of HAIs. In the healthcare system, HAIs are considered among the most common and serious health problems. However, the occurrence of HAIs differs between different types of clinical departments within the hospital. Recently, the risk of HAIs has been increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…They were asked to state whether waste segregation is the work of only casual workers. Their responses are shown in Table 27 (8) of the respondents strongly agreed with the opinion that waste segregation in the ward where they worked was the duty of the casual worker, 12% (12) agreed, 6% (6) neither agreed nor disagreed, 38% (38) disagreed, and 36% (36) strongly disagreed. All personnel participate in the generation of clinical waste within the hospital, and it is the responsibility of all to segregate the waste generated well.…”
Section: Waste Segregation Is the Work Of The Casual Workers Onlymentioning
confidence: 95%
See 1 more Smart Citation
“…They were asked to state whether waste segregation is the work of only casual workers. Their responses are shown in Table 27 (8) of the respondents strongly agreed with the opinion that waste segregation in the ward where they worked was the duty of the casual worker, 12% (12) agreed, 6% (6) neither agreed nor disagreed, 38% (38) disagreed, and 36% (36) strongly disagreed. All personnel participate in the generation of clinical waste within the hospital, and it is the responsibility of all to segregate the waste generated well.…”
Section: Waste Segregation Is the Work Of The Casual Workers Onlymentioning
confidence: 95%
“…Infection control addresses factors related to the spread of infections within the health care setting (whether patient-to-patient, from patient to staff, and from staff to patients, or among staff), including prevention (via hand hygiene/ hand washing, cleaning/ disinfection/ sterilization, vaccination, surveillance), monitoring/ investigation of demonstrated or suspected spread of infection within a particular health-care setting (surveillance and outbreak investigation), and management (interruption of outbreaks) [3]. Driven by several emerging factors in the field of global public health, there is a need to support the development and strengthening of IPC capacity to achieve resilient health systems, both at the national and facility levels [4] However, a large proportion of HAIs are preventable and there is a growing body of evidence to help raise awareness of the global burden of harm caused by these infections [5,6] including strategies to reduce their spread [7,8].There is a growing body of evidence on the global burden of harm caused by HAI, as well as the strategies necessary for its reduction [9,10]. Numerous studies document the pivotal role of healthcare workers (HCWs) hands in the propagation of microorganisms within the healthcare environment and ultimately to patients [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In developing nations, 98% of the world's estimated 5 million newborn fatalities occur, with hospital-acquired infections accounting for 1.6 million fatalities. In the USA, 75,000 of 722,000 patients who had an infection at the time of their stay in an acute care hospital died as a result of a nosocomial illness in 2011 [3] . In Iran, hand hygiene compliance increased significantly after the development and implementation of an infection control link nurse program.…”
Section: Need For the Studymentioning
confidence: 99%
“…Despite the progress in medical advancements and treatments, there has been a global rise in the occurrence of hospital-acquired infections (HAIs) [ 1 ]. According to the World Health Organization (WHO), the prevalence of HAIs in hospital settings worldwide ranges from 6% to 19.5% [ 2 ]. Recent studies have reported HAI prevalence rates of 3.5% in the United States [ 3 ].…”
Section: Introductionmentioning
confidence: 99%